Two new species and a new record of Metacirolana Kussakin, 1979 (Crustacea: Isopoda: Cirolanidae) from Indonesia - Sidabalok, Conni M.; Bruce, Niel L. (Zootaxa, 2018)
Two new species of Metacirolana from coral reefs in Indonesia are described and Metacirolana spinosa (Bruce, 1980) is recorded for the first time in Indonesia. Metacirolana lombok sp. nov. and Metacirolana mioskon sp. nov. show similarities with several other species of Metacirolana forming a species group within the genus, characterized by small body size (2.0–3.5 mm), smooth body surfaces, weakly produced rostrum, lack of dorsal carinae and abundant chromatophores.